LEARNING MEDIA PALANG AJIB (PAPAN LANGKA AJAIB) TO EASY IN UNDERSTANDING THE METERIALS OF RELATIONSHIP AND FUNCTIONS - Brenda Indah Nirmala; Muhammad Ikram An-Nurdin; Muhamad Yafis Kahfi Muttaqin; Novi Aisy Fajriati; Agus Miftakus Surur (FKIP Universitas Muhammadiyah Tangerang, 2022)
The teaching and learning process needs the media that plays a role in it. Decreased student understanding in learning results in decreased student learning outcomes. The media that is considered appropriate and in accordance with current conditions is the Palang Ajib learning media (Papan langka Ajaib). This media is used to teach in the classroom where the teacher usually only uses books and boards. The research method used is development research with the ADDIE model. The research begins with an analysis of the needs needed in the field, then continues with making appropriate media designs. The next step is to develop the media based on the designs that have been made. The next step is implementation and evaluation. By using this learning media, it is intended to make the learning process more effective and not boring. In addition, there is another purpose, namely this media is made to make it easier for students to learn and understand the material Relations and Functions. The process of making this learning media using materials and tools can be found in the surrounding environment. In addition, the benefits of this media make it easier for students to learn and understand Relations and Functions material, hone children's creativity, increase children's interest and enthusiasm in studying Relations and Functions material.